Hubungan Antara Kondisi Lingkungan Sekolah Dengan Aktivitas Belajar Siswa SMA Shailendra Palembang - Cara, Farista Sanis; Puspita, Yenny; Wahidy, Achmad (Indonesian Research Journal on Education, 2023)
This study aims to determine the explanatory learning outcomes of class VIII students of SMPNegeri 1 Gelumbang using the brain writing method. The research method used is an experimental type of post-test control design. In this study using a test technique. The final result of the evaluation of student learning data using the t-test. That is, if the required sig value > 0.05 then the data will be homogeneously distributed. If the value of sig < 0.05 then the data distribution is not homogeneous. The significant value obtained from the calculation results is the sig value of 3.418 which means > 0.05. Therefore, the researcher concludes that learning brain writing has an effect on the writing skills of the eighth grade students of SMP Negeri 1 Gelumbang